Teste de potência para clostridium sordellii em vacinas comerciais contra clostridioses - Glaucia Mansur Balsamao (2001)
Twelve commercial vaccines used in Brazil which contain Clostridium sordellii have been compaired with a standard vaccine, produced in United States of America. A method was used to estimate the protection of guienea pigs whitch were immunized with 1/5 of the dose used in bovines containing 100LD50 of spores in 5% of CaCl2. All tested vaccines were sterile and didnt induce disease. As far as efficacy is concerned, from those 13 tested vaccine, only the standard vaccine and three commercial vaccines reached the required quality. Two vaccine labelled T6 and T8 gave identical results as the standard vaccine protecting all the challenged animals. The vaccine labelled T10 after being re-tested was considered efficient.